2019
DOI: 10.4236/jep.2019.1012097
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality Model for Streams: A Review

Abstract: Six main public domain water quality models which are presently available for Rivers and streams are being captured in this article. These main models could produce important results if they are used in the correct manner, because they are different in terms of assumptions, strength and weaknesses, processes they represent, modeling capability and data input requirements. The Model review discussed includes, water quality analysis simulation program (WASP7), simulation catchment (SIMCAT), quality simulation al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…However, for the Awash Basin, it was proposed to select the public (i.e., free available) models so as to avoid this limitation. Accordingly, six in-stream models were considered for screening the applicable one: (1) INCA (Integrated Catchment) (Whitehead et al, 2018(Whitehead et al, , 2021(Whitehead et al, , 1998, (2) WASP8 (Water Quality Analysis Simulation Program) (Ranjith et al, 2019), (3) QUASAR (Quality Simulation along Rivers) (Cox, 2003;Ranjith et al, 2019), (4) QUAL2KW (Bui et al, 2019;Chapra et al, 2015;Pramaningsih et al, 2020), ( 5) CE-QUAL-RIVI, and (6) SIMCAT (Simulation of Catchments) (Cox, 2003;Ranjith et al, 2019).…”
Section: Screening the Best Applicable Modelmentioning
confidence: 99%
“…However, for the Awash Basin, it was proposed to select the public (i.e., free available) models so as to avoid this limitation. Accordingly, six in-stream models were considered for screening the applicable one: (1) INCA (Integrated Catchment) (Whitehead et al, 2018(Whitehead et al, , 2021(Whitehead et al, , 1998, (2) WASP8 (Water Quality Analysis Simulation Program) (Ranjith et al, 2019), (3) QUASAR (Quality Simulation along Rivers) (Cox, 2003;Ranjith et al, 2019), (4) QUAL2KW (Bui et al, 2019;Chapra et al, 2015;Pramaningsih et al, 2020), ( 5) CE-QUAL-RIVI, and (6) SIMCAT (Simulation of Catchments) (Cox, 2003;Ranjith et al, 2019).…”
Section: Screening the Best Applicable Modelmentioning
confidence: 99%
“…Hence, proxy parameters, like electrical conductivity levels, are observed and linked to variations in the concentration of conservative parameters within the river system. This approach is widely noted in the majority of water quality parameter studies found in the literature (Ranjith et al 2019). In contrast, non-conservative water quality parameters, like nutrients, can interact chemically with the environment, causing concentration changes over time.…”
Section: Model Environment and Water Quality Parametersmentioning
confidence: 99%
“…QUAL2KW modeling is a one-dimensional, steady-state flow modeling approach that is compatible with Windows operating systems (Parveen & Singh, 2016). Qual2Kw is able to simulate water quality parameters including temperature, conductivity, inorganic solids, dissolved oxygen, CBODslow, CBODfast, organic nitrogen, ammonia, nitrite, nitrate, organic phosporus, inorganic phosporus, pathogens, alkalinity, pH (Maghfiroh, 2016) (Ranjith et al, 2019). One advantage of QUAL2KW modeling is its ability to simulate both point source and non-point source pollution for various water quality parameters.…”
Section: Introductionmentioning
confidence: 99%